Productivity Analysis of Digging, Loading, and Hauling Equipment in Overburden Removal Activities at PT. Anugrah Borneo Sinergy in Keramat Mina field, South Kalimantan, Indonesia - Muhammad Rusdi Taufiq; Fairus Atika Redanto Putri; Yazid Fanani (Journal of Earth and Marine Technology (JEMT), 2024)
This study evaluates the productivity of loading and hauling equipment at Anugrah Borneo Sinergy Ltd., explicitly focusing on compatibility between these units and identifying obstacles in overburdening material transfer activities. Employing a direct observation method at pit 1 in Keramat Mina Village, this research spanned a day shift from August 20 to September 20, 2022. Productivity measurements were taken for the Sany SY 365 H Excavator and the Hino 500 FM 260 JD Dump Truck, alongside employee interviews for supplementary data. Results indicate that the excavator's productivity varied daily, averaging 136.07 Bcm/hour, while the dump truck averaged 56.19 Bcm/hour over the same period, both below the target of 170 Bcm/hour. Initial compatibility assessment yielded a match factor of 0.83, which improved to 1.18 after optimizing cycle times. Simulating the compatibility with an additional hauler resulted in a perfect match factor of 1. Key obstacles included extended waiting and haul times, inefficiency, and an imbalance in the number of loaders versus haulers. Recommendations to enhance productivity involve optimizing loading efficiency and reducing haul, return and wait times. Post-optimization, productivity improved significantly, reaching 163.28 Bcm/hour for loaders and 88.29 Bcm/hour for haulers, thus meeting production goals. Adding another hauling unit could sustain these improvements by achieving optimal equipment compatibility.